Community Service in an Effort to Introduce Indonesian Accounting System to Thai Students - Komara, Acep; Mahadianto, Moh. Yudi; Yulianto, Agung; Hadiyati, Siti Nur; Fatimah, Siska Ernawati; Srisuk, Prattana; Astillero, Marlon Rael (JOURNAL OF SUSTAINABLE COMMUNITY SERVICE, 2025)
Accounting is a science that has its own unique features, where every country applies accounting principles in accordance with standardized international norms. Accounting plays an important role for countries as it can be considered the language of business, revealing the financial performance of enterprises. The diversity in accounting applications across nations inspired our interest in exploring the differences between Indonesian and Thai accounting practices through community service involving lecturers and students from Thai Global Business Administration Technological College Thailand (TGBC Thailand). This international community service initiative included six lecturers from Indonesia, five lecturers from TGBC, and 15 students, at TGBC. The purpose of this international community service was to educate participants about and introduce accounting practices applied in both Indonesia and Thailand. This activity is expected to provide additional insights and applications of new knowledge in the field of accounting.